(untitled) (Research, Society and Development, 2020)
Objective: To verify the existence of a relationship between sociodemographic variables, symptoms of depression, overload, quality of life on the capacity for self-care. Method: Cross-sectional study, developed at the Elderly Health Care Center in Niterói. A sociodemographic questionnaire, a revised Self-Care Assessment Scale, a Zarit overload scale, a depression scale from the Center Epidemiological Studies - Depression and Quality of Life Assessment were used. Data treated in the statistical program R. Descriptive and inferential analysis was applied. Results: Descriptive analysis showed a predominance of women, daughters of the elderly and 60.8% shared the care. The univariate analysis showed the influence of the role of caregiver and its environment on the rates of depression and quality of life. Multivariate analysis showed that the rates of increased depression are inversely proportional to self-care. Conclusion: The basic conditioning factors directly influence the capacity for self-care, especially depressive feelings and the environment where the caregiver lives.